Analysis Of Factors Inhibiting Employees From Reading Kwh Post-Paid Meters In The Field (PT. IDO SINERGI) - Ahistasari, Asih; Febrian Ramadhan; Irman Amri; Ashar (PT. SAFARI AMALIA, 2023)
PT. PLN (PERSERO) as a State-Owned Enterprise to provide the best service for all electricity users in Indonesia, PLN which takes care of all aspects of electricity for the public interest throughout Indonesia. At first PLN used postpaid electricity kwh recording calculating tool, where the kWh meter recording used analog system. Several problems and complaints from the public regarding the use postpaid electricity in the form of late payments, meter recording errors and erratic bills, PLN specifically for the Sorong branch in collaboration with PT. Ido Sinergi as a service provider, especially in the work of recording kwh meters, must be able to provide satisfaction to PLN as its partner. When recording kwh meters, factors that often hinder activities in the field such as fence locks, closed houses, empty houses, tall meters, opaque meters, fierce animals, unloading meters, lost meters other unexpected factors. The purpose this study to find out the various factors inhibiting kWh meter readings in the field, the data obtained was then processed using data analysis tool used to answer the research problem using the Pareto Diagram. The conclusion from this study is that the inhibiting factors for reading kwh meters in the field are fence locks, closed houses, empty houses, tall meters, opaque meters, fierce animals, unloading meters, missing meters with a total of 598 constraints from 20,580 customers, along with the percentage pk 31%, rt 13%, rk 15%, mt 7%, mbrm 15%, hg 3%, mb 10%, mh 7%.